EXAFS and X-ray diffraction study of LaCoO3 across the spin-state transition. (May 2016) - Sikolenko, V V; Troyanchuk, I O; Efimov, V V; Efimova, E A; Tiutiunnikov, S I; Karpinsky, D V; Pascarelli, S; Zaharko, O; Ignatov, A; Aquilanti, D; Selutin, A G; Shmakov, A N; et al.
Abstract: A combined high-resolution Co K -edge extended x-ray absorption fine structure (EXAFS) and high-resolution X-ray powder diffraction (XRD) study has been performed to clarify the detail of anomalous behavior of temperature-dependent magnetic susceptibility curve on the LaCoO3 across the spin-state (∼120 K) transition. According to XRD analysis, the Debye-Waller factor of Co-O bond exhibit rapid growth below 20 K whereas the temperature dependence of the average Co-O bond length shows linear behavior from 10 K to 400 K. The EXAFS data show an anomalous decrease of the Co-O bond lengths with respect to those obtained by XRD. No local distortion of CoO6 octahedral as temperature increases up to 400 K has been detected.